Socialization of the Covid-19 vaccine for children on the acceptance of parents - Adhani, Abrar; Anshori, Akhyar; Nasution, Nurhasanah (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
This study aims to find out how the influence of the socialization of the Covid-19 vaccine program on children by the Indonesian government has on the level of parental acceptance in Medan City. The research was conducted using a quantitative approach to 200 parents of elementary school students. Data collection was carried out through questionnaires and data analysis was carried out by testing hypotheses through t-test and f-test and the coefficient of determination. The results of the study found that the outreach carried out by the government about the benefits of the Covid-19 vaccine for children was not effective. This can be seen from the results of the coefficient of determination test, whether there is a level of trust of respondents in the information on the Covid-19 vaccine and whether there is a child's behavior in implementing the health protocol which is carried out simultaneously. regarding the respondent's attitude regarding Covid-19 vaccination for children, the respondent's acceptance rate was 14.1%. This shows the failure of the Indonesian government in socializing the benefits of the Covid-19 vaccine for children in efforts to prevent Covid-19.